Evaluation of anticonvulsant activity of angiotensin receptor antagonists in an animal model - Jadhav, Asha D.; Jadhav, Rakesh R.; Padwal, Sudhir L.; Jadhav, Swapnil S.; Kale, Anand S.; Gade, Prakashchandra R. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Epilepsy is common chronic disorder in clinical practice and there was some studies which shows brain renin angiotensin system may be involved in upregulation of seizures hence present study was planned to investigate whether angiotensin II AT1 receptor antagonists possess anticonvulsant activity in experimental animals. Methods: The anticonvulsant activity of angiotensin receptor antagonists, losartan (50 mg/kg), telmisartan (30 mg/kg) and candesartan (20 mg/kg), were administered intraperitoneally to the mice and evaluated by using maximum electroshock (MES) and pentylenetetrazol induced seizures (PTZ) seizure methods. The standard was taken as phenytoin for MES and diazepam for PTZ method. Motor impairment of performance was assessed by the inverted screen test and spontaneous motor activity with digital actophotometer. Results: Losartan demonstrated the anticonvulsant efficacy in MES and PTZ models. Telmisartan and candesartan have anticonvulsant activity in MES induced seizures, but did not show protection against pentylenetetrazol induced seizures. Losartan at dose 50 mg/kg prolonged the mean latency to convulsion (p<0.01) and mean number of convulsions also significantly reduced (p<0.05) convulsions in the mice. Telmisartan and candesartan at dose 30 mg/kg and 20 mg/kg respectively showed significant prolongation in mean latency to convulsion (p<0.05). None of the test drugs i.e. angiotensin receptor antagonists showed significant motor impairment. Conclusions: Angiotensin receptor antagonists: losartan, telmisartan and candesartan had showed anticonvulsant activity in PTZ and MES seizure methods. The exact mechanism of action of their anticonvulsant action not precisely known and hence there is more studies need to test it in various other animal anticonvulsant models.